Celtic language writing matters in Hispania, Gaul and Italy (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The first of these three separate studies deals with the layout and contents of Celtic spindle-whorl inscriptions proposing, in particular, a new reading Kat‘te’uai for the ancient text from Parre and a new analysis for the longer text from Segeda. Object of the second study are the Celtiberian u vowels, their origins (IE inheritance, dialectal Celtic sound change, and graphic support after a velar stop) and their twofold notation, namely as in addition to normal . The third and last study explains the differ- ent sources of the palatal glides often appearing in topo- and ethnonymic forms. New analyses of several Old Celtic and Celtiberian forms are offered all through the article.
Keywords: Spindle-whorls; Celtic Languages; Coin Legends; Orthography; Parre